Pain prevalence and pain management in children and adolescents in an italian third level pediatric hospital: a cross-sectional study - Giuliano Marchetti; Alessandro Vittori; Marco Cascella; Ilaria Mascilini; Simone Piga; Emiliano Petrucci; Aurora Castellano; Roberta Caruso; Elisa Francia; Francesca Stocchi; Franco Marinangeli; Alessandro Inserra; et al. (BMC, 2023)
Abstract Background In 2016, we performed a one-day investigation to analyze the prevalence of pain, pain intensity, and pain therapy in the Departments of Surgery and Onco-Hematology of the Ospedale Pediatrico Bambino Gesù. To improve the knowledge gap highlighted in the previous study, refresher courses and even personalized audits have been carried out during these years. The purpose of this study is to evaluate if, after 5 years, there have been improvements in the management of pain. Methods The study was conducted on 25 January 2020. Pain assessment, pain therapies, pain prevalence and intensity in the preceding 24 h and during the recovery period were recorded. Pain outcomes were compared with previous audit results. Results Out of the 63 children with at least one documented pain assessment (starting from 100 eligible), 35 (55.4%) experienced pain: 32 children (50.7%) experienced moderate /severe pain while 3 patients (4%) felt mild pain. In the preceding 24 h, 20 patients (31.7%) reported moderate/severe pain while 10 (16%) reported moderate or severe pain during the interview. The average value of the Pain Management Index (PMI) was − 1.3 ± 0.9 with a minimum of -3 and a maximum of 0. 28 patients (87%) undergoing analgesic therapy for moderate/severe pain had a PMI of less than 0 (undertreated pain), while 3 patients (13%) scored value of 0 or higher (adequate pain therapy), 4 patients (12.5%) received multimodal analgesia with opioids and 2 patients (6%) opioids alone. Time-based therapy was prescribed to 20 patients (62.5%), intermittent therapy was prescribed to 7 patients (22%) and 5 patients (15.5%) did not receive any therapy. The prevalence of pain was higher during hospitalization and 24 h before the interview, while at the time of the interview, the proportion was the same. In this audit, the daily prescription modality of the therapy had some improvements (time-based: 62.5% vs. 44%; intermittent: 22%vs 25%; no therapy: 15.5% vs. 31%). Conclusion Pain management in hospitalized children constantly requires special daily attention from health professionals aimed at mitigating the components of intractable pain and resolving those of treatable pain. Trial registration : This study is registered with ClinicalTrials.gov, number (NCT04209764), registered 24 December 2019, https://clinicaltrials.gov/ct2/show/NCT04209764?term=NCT04209764&draw=2&rank=1 .